Efficient induction of tetraploids via adventitious bud regeneration and subsequent phenotypic variation in Acacia melanoxylon - Shenxiu Jiang; Yufei Xia; Aoyu Ling; Jianghai Shu; Kairan You; Shun Wang; Dingju Zhan; Bingshan Zeng; Jun Yang; Xiangyang Kang (Plant Methods)
Abstract Background acacia melanoxylon is an important species for establishing pulpwood plantations due to its high application value in engineered wood products. However, the lack of a well-established in vitro regeneration system has severely constrained its industrial-scale propagation and the induction of tetraploids. Results In this study, using the superior A. melanoxylon clone SR3, an in vitro regeneration system using a bud-bearing stem segment was established. A DKW medium supplemented with 0.5 mg/L 6-BA, 0.1 mg/L IAA, and 0.2 mg/L NAA was determined as the optimal differentiation medium. Adding 0.5 mg/L IBA and 0.25 mg/L NAA to the 1/2 MS medium produced a higher rooting percentage and root number. To determine the optimal timing for tetraploid induction in A. melanoxylon, morphological, cytological, and flow cytometric analyses were conducted on the swollen tissue at the base of the bud-bearing stem segment. On the 5th day of preculture, white callus tissue was observed, characterized by vigorous cell division and the highest G2/M-phase cell content in the adventitious bud primordia. After colchicine treatment, the tetraploid induction efficiency on the 5th day of preculture was significantly higher compared to the 4th or 6th day. The highest induction rate of 12.26 ± 0.80% was achieved with 100 mg/L colchicine for 72 h on the 5th day of preculture. Furthermore, tetraploid A. melanoxylon exhibited morphological traits such as reduced plant height, leaf number, and stomatal density. Conclusions This study establishes a stable and effective method for in vitro tetraploid induction in A. melanoxylon, providing theoretical and technical support for polyploid breeding and laying the groundwork for subsequent triploid development.